Pengaruh Media Animasi Audio Visual Terhadap Karakter Disiplin Anak di RA Insanul Fitroh Palembang - Santia Santia; Leny Marlina; Lidia Oktamarina (PIAUD Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah, 2020)
ABSTRACKDiscipline is a very important character to be instilled in children. Discipline in early childhood does not appear suddenly, but starts through a routine that is done consistently every day. The problem in this research is that the media is too monotonous. This study aims to determine the effect of audio-visual animation media on disciplinary characters in RA Insanul Fitroh Palembang. The research method used is Pre experimental design with One Group research design pre test post test. The study population used in this study were all group A in RA Insanul Fitroh Palembang, which amounted to 10 children. Data collection using documentation and observation, analysis results with t-test X2calculated = 0.23 <X2table = 3.841 and hypothesis testing the results of tcount = 10.045> ttable = 2.101 Thiproves that there is a significant influence between audio-visual animation media on discipline characters RA Insanul Fitroh son of Palembang.Keywords: Media, animation, Audio visual, disciplin